BARRIERS PERCEIVED BY THE DENTISTS IN PROVIDING ORAL HEALTH CARE TO THE ELDERLY: A NARRATIVE REVIEW - Monika Werdiningsih; Melissa Adiatman; Iwany Amalliah Badruddin (Universitas Baiturrahmah, 2022)
Introduction: Demographic population changes towards the aging population can impact dentists to provide oral health care. Oral health care needs and problems among the elderly differ from those in the general population. They require consideration and optimal treatment planning. In providing oral health care to the elderly, dentists may encounter various barriers, and it may become challenging for dentists to meet elderly needs and overcome their oral health problems. Review: Dentists perceive several factors as barriers and challenges in providing oral health care to the elderly, such as knowledge in geriatric dentistry, experience providing the treatment, complexity of treatment, practical barriers, and financial aspect, thus making dentists not sufficiently prepared to provide oral health care for the elderly. Conclusion: Barriers perceived by dentists in providing oral health care to the elderly need to be addressed to increase the readiness of dentists and overcome the barriers so they can provide oral health care optimally, meet the elderly needs, and overcome their oral health problems.